SURGICAL PROCEDURE FOR PELVIC PERIACETABULAR BONE TUMOR DEFECTS - Vyrva, Oleg; Malyk, Roman; Golovina, Yanina (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Pelvic bone tumor and traumatic injuries are causes to a numeric of diagnostic, treatment and subsequent obtaining of positive functional results problems, which significantly affects the patientʼs quality of life. The most prognostically difficult are acetabulum areas defects. Its adequate restoration affects the further walking function. Goal. To develop a surgical reconstruction of the periacetabular tumor resection defects. Methods. A new surgical reconstruction procedure of the pelvic periacetabular defects were developed and submitted. It consists in using of artificial material polyethyleneterephthalate («Attachment tube») replacing, which is pre-filled with bone allograft and sutures transosseously fixed to the pubic bone or to the pubic/ischial bones. Another «Attachment tube» fragment is used to fix the femur head to the indicated allograft implant. The strength and bioactive characteristics of the «Attachment tube» in combination with bone allograft make it possible to obtain the equivalent of the acetabulum and restore the full weight bearing and walking function with a certain range of motion in the restored acetabulum area. Results. The proposed method was clinically tested on 9 patients with evaluated follow up. Satisfactory functional results were obtained: (52.6 ± 20.0) % on the MSTS scale. Complications were analyzed. Conclusions. The use of novel surgical procedure for pelvic periacetabular bone tumor defects has a number of advantages over the existing ones. The biological materials using, restoration of anatomical relations in the «hip joint» makes it possible to restore the lower limb function with a good range of motion. The obtained results prove authorʼs method using can give acceptable results in the treatment of periacetabulum tumor leasions patients.